Pengaruh Simpanan Saham terhadap Ketahanan Lembaga pada KSP Kopdit Guru Kelubagolit Adonara - Anastasia Ina Boro; Konstantinus Pati Sanga; Yoseph Darius Purnama Rangga (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to examine and analyze the effect of stock savings on the resilience of the KSP Kopdit Guru Kelubagolit Adonara institution. This research is a type of quantitative research with an associative approach. The data used in this research is financial report data consisting of the number of shares deposits and remaining business results of KSP Kopdit Guru Kelubagolit Adonara for the 2014 – 2023 financial year. The data analysis method used in this research is simple linear regression analysis. The results of this research show that the sig. (p-value) of the stock savings coefficient is 0.001 < 0.05, with a calculated t value of 5.029 > t table 1.81246. This shows that stock savings have a significant effect on Remaining Business Results, with a regression coefficient for Stock Savings of 0.168, which shows that every increase in Stock Savings will increase SHU by IDR 0.168. This means that there is a positive relationship between Share Savings and SHU, where an increase in Share Savings will lead to an increase in the cooperative's financial performance as measured through SHU.